Correction of Point-of-Care INR Results in Warfarin Patients. Issue 1 (March 2016) - Richter, Christopher; Taylor, James; Shuster, Jonathan
N/A: Background: The measurement of international normalized ratio (INR) may be performed by venous blood draw and use of a standard laboratory or by fingerstick, using a point-of-care (POC) device such as the CoaguChek XS (Roche Diagnostics, Indianapolis, Ind), and the CoaguChek XS has been validated to meet the International Organization for Standardization performance requirements. Overview: The goal of this study was to determine a correction factor for Coaguchek XS INR levels to a predicted venipuncture (VP) INR level. Methods: At the end of an anticoagulation clinic visit when a patient had an INR of 4 or greater, 2 INR results existed, which were from the Coaguchek XS meter and a VP INR from the laboratory. The data were then discreetly recorded as a quality control for our clinic. The data were analyzed for possible significant trends between the 2 types of INR results. Results: The equation that was determined to be the best fit to the data was 0.621 × POC + 0.639 = estimated VP. The overall root mean square error for the calculated correction was 0.44 INR. The root mean square errors were 0.41 and 0.58 for the 4 to 5.9 and 6 to 7.9 POC INR groups, respectively. Conclusions: The calculation that was derived in this study is not a surrogate for VP INR in this clinic. However, the estimation of the INR may be useful clinically in guiding decision making in the future.